HETEROSIS FOR YIELD AND YIELD ATTRIBUTED TRAITS IN RICE (Oryza sativa L.) - GOKULAKRISHNAN, J. (Horticultural Biotechnology Research)
Rice is the foremost food crop among cereals and it is staple food crop providing high calories for the people of South East Asia. The Objectives of the study was the extent of heterosis components of grain yield in F1 hybrids. The Materials for this study considered of parents and thirty F1 hybrids derived from crossing of three cross lines viz., IR58025A, IR62829A and PUSA3A and ten testers. Pollen and spikelet fertility revealed the identification of ten testers. For heterosis studies majority of the crosses showed positive heterosis for the characters viz., productive tillers, filled grains per panicle, spikelet fertility, thousand grain weight, grain yield per plant, grain length, grain breadth, grain L/B ratio, kernel L/B ratio, milling recovery, head rice recovery, and amylose content. Negative heterosis were recorded for the characters namely days to first flowering, plant height, panicle length, kernel length, kernel breadth and alkali digestion value. Hybrids IR58025A ´ ASD19, IR62829A ´ ASD16, PUSA3A ´ IR42 were found to record high per se performance, higher percentage of standard heterosis for majority of the traits.